Surviving acute myocardial infarction: survivin expression in viable cardiomyocytes after infarction. Issue 12 (24th November 2004) - Santini, D; Abbate, A; Scarpa, S; Vasaturo, F; Biondi-Zoccai, G G; Bussani, R; De Giorgio, F; Bassan, F; Camilot, D; Di Marino, M P; Feroce, F; Baldi, F; et al.
Abstract : Background: Apoptosis is a key feature in postinfarction remodelling leading to progressive myocyte loss. Both proapoptotic and antiapoptotic factors contribute to the delicate balance between death and survival. The survivin pathway has emerged as essential in the control of apoptosis, although its role in heart disease is unknown. Aim: To evaluate survivin expression after acute myocardial infarction (AMI). Methods: Survivin expression was assessed immunohistochemically in the peri-infarct and remote viable myocardium in 17 consecutive patients who died 1–30 weeks after AMI and in four control hearts. Results: Survivin was expressed by myocytes in the peri-infarct area in eight patients and in the remote region in 13 patients. The rate of survivin expression after AMI was significantly higher in the remote versus peri-infarct regions and compared with control hearts. Its expression was inversely associated with the presence of dilated cardiopathy and of apoptosis, independently from the gross pathology infarct size. Conclusions: Survivin myocardial expression after AMI may be associated with the survival of at risk myocardium and may be indicative of more favourable remodelling after AMI. These findings identify a potential new target for the treatment of postinfarction remodelling.